Corporate technology for the implementation of an automated system: functional, technological and methodological aspects - Olga Maslennikova; Olga Borisovna Nazarova (Открытое образование (Москва))
The purpose of the study is to form a methodological justification for the pedagogical model of the individual trajectory of professional development of bachelors and masters for the implementation of the stages of creating an automated system based on the principles of continuity and experimental verification of its application in the educational process of the university in accordance with the requirements of IT departments, vendors and employers. It is shown that there is a gap between the socio-economic order for the training of IT specialists with high professional competence in the field of information systems and the insufficient level of targeted formation of their readiness to implement the stages of creating automated systems. In addition, the lack of methods and practical recommendations for the implementation of such systems in the context of maximum preservation of corporate standards and taking into account the requirements of Russian legislation, as well as specialists competent in these matters, determined the feasibility of conducting the study in two aspects - functional-technological and pedagogical.Methods and materials. The key methods are structural-functional and process modeling, interactive methods of organizing the educational process (project method, etc.). The research materials include a functional model for developing a corporate technology for implementing an automated system in the form of a function tree.Results. The results present a model of causes and factors determining the success of the projects for the implementation of the automatization systems. The role of the factor "qualification of the executing team" and the possibilities of the educational environment of the university to influence this factor are considered. The pedagogical aspect of the research problem is determined by the methodological justification for conducting students' project work within a number of disciplines for training bachelors and masters in the field of "Applied Informatics". The description of the structure and requirements for students' projects gives an idea of the level of competencies being formed, their consistency with the work functions of specialists in the field of information systems.Conclusion. At this stage of work on the research problem, its dual nature was determined. On the one hand, modern IT projects require their own technologies and management methodologies, which should change from project to project, so it is important to have practical recommendations for the development of corporate technology for the implementation of an automated system. On the other hand, one of the success factors of the project for the implementation of an automated system is the "Project Implementation Team", its level of qualification. This factor is successfully determined and influenced by educational institutions responsible for training specialists in this field. In this direction, the project method plays a key role. It ensures the development of communication skills, the ability to independently pose a problem and develop a way to solve it together. Methodological aspects and practical results, generalizing the pedagogical model for training bachelors in the field of creating automated systems presented in the work, as well as the development of corporate technology for the implementation of information systems, are reflected in three electronic multimedia educational publications "Portfolio of Software Engineering Projects", "Theory and Practice of Implementation of IS", "Theory and Practice of Maintenance of IS".